Historical and systematic interpretations of the regulations on guilt, the inherent condition of the legal liability - URSU, Viorica (Journal of Social Sciences, 2019)
The principle of liability for guilt has become one of the central principles of the legal reality with the development of the civilization, when the human life and personal freedom have gained the highest value. The need to protect the fundamental human rights implies the existence of some clear rules of conduct. These rules should be even stricter when it comes to those situations where the human destiny is at stake. The legal processes must be organized so that no person should suffer unjustly. This was exactly the purpose of establishing the concept of the guilt in the contemporary systems of law and the definition and analysis of the concept of guilt become so important. The legal concept of guilt is the only guarantee that no person can be judged according to his/her appearance, that no person will be convicted until his/her case is meticulously examined as in the aspect of the objective elements, as well as in the aspect of subjective elements. Thus, the guilt is the binding element of any form of the legal liability. In this article, we intend to conduct an analysis of the guilt, which is the condition of the legal liability. Due to the fact that this research topic is quite complex and present, it is important to present the regulatory framework of the subject in terms of its historical evolution and the contemporary law, both domestic and foreign.